Simultaneous endovascular revascularization of external iliac artery dissection and transplant renal artery stenosis in a recent renal allograft recipient - Vijayvergiya,Rajesh (2021)
Abstract Various vascular complications following renal transplantation include renal artery and vein thrombosis, renal artery stenosis, pseudoaneurysm, and iliac artery dissection. Transplant renal artery stenosis (TRAS) is the most common, while iliac artery dissection is the rarest of these various vascular complications. We describe an elderly male, who had both external iliac artery dissection and TRAS at 2 months following renal transplantation. He underwent successful percutaneous endovascular intervention of both complications. The post-intervention course was uneventful, with improvement in graft renal functions and left lower limb perfusion.